Theoretical ab Initio Study on Cooperativity Effects between Nitro π‐hole and Halogen Bonding Interactions. Issue 9 (10th April 2019) - Galmés, Bartomeu; Martínez, Daniel; Infante‐Carrió, Maria F.; Franconetti, Antonio; Frontera, Antonio
Abstract: This article analyzes the interplay between nitro's π‐hole and halogen–bonding (XB) interactions in nitroarenes. Remarkable cooperativity effects are observed when π–hole and XB interactions coexist in the same complex. The nitroarene presents two π‐holes, one approximately over the N atom of the nitro group and the other over the aromatic ring, being the former more positive. The interplay between both interactions has been analyzed in terms of energetic and geometric features of the complexes, which are computed at the RI‐MP2/def2‐TZVPD level of theory. Molecular electrostatic potential (MEP) surface calculations have been used to explore the variation of the MEP values at the π‐hole upon the formation of halogen bonding interactions between the nitroarene and CF3 X (X=Cl, Br and I) molecules. In addition, the Bader's theory of atoms in molecules" (AIM) is used to characterize the interactions by means of the distribution of bond critical points and bond paths and to analyze their strengthening or weakening depending upon the variation of charge density at critical points. The aforementioned computational methods are adequate to examine how these interactions mutually influence each other. Natural bond orbital (NBO) and noncovalent interaction plot (NCIPlot) computational tools have been also used in some representative complexes to further analyze cooperativity effects. Finally, the Cambridge Structural Database (CSD) is used to provide some experimental evidence. Abstract : The interplay between nitro π‐hole and halogen‐bonding interactions in nitroarenes is analyzed. Remarkable cooperativity effects are observed when both interactions coexist in a complex. Nitroarene presents two π‐holes, one approximately over the N atom of the nitro group and the other over the aromatic ring, the former being more positive.